Gravitating toward supply chain 4.0. Issue 1 (31st December 2022) - Sultana, Nahida; Nusrat, Mansura; Akter, Tahmina; Khatun, Merina
Abstract: The present study inspects correlations among different industries' intention to tackle supply chain recovery challenges, and the correlations among diverse industries' desire to use supply chain 4.0 technologies. Primary data for the study have been accumulated through a structured questionnaire to elicit responses from supply chain managers and executives. To examine the obtained data, descriptive statistics, Cronbach alpha, exploratory factor analysis, and Kruskal–Wallis test were used. There is no significant relation among different industries' intention to tackle supply chain recovery challenges and to adopt industry 4.0 technologies. However, the Food and Beverage industry showed the highest level of intention to both tackle the impact of supply chain disruption, and adopt industry 4.0 technologies to ensure more resilient supply chain post Covid-19. This study is the very first attempt to identify the intention of different industries to adopt supply chain 4.0 technologies to combat challenges stem from the supply chain disruptions caused by COVID-19.